Compliance with the Covid-19 Protocol for Pregnant Women in Pagelaran - Parastika Anggun Fauzia; Leersia Yusi Ratnawati; Rina Sutjiati (Jurnal Kesehatan Masyarakat, 2023)
The COVID-19 pandemic resulted in more than 30 million deaths in 2020. Pregnant women are a vulnerable group. They tend to be at risk of contracting and experiencing complications that can affect pregnancy and fetal development. This research aims to analyze behavioral factors that influence compliance with the COVID-19 protocol for pregnant women using the health belief model approach in the working area of the Pagelaran Health Center. This research is a cross-sectional study of pregnant women in the Pagelaran health center. The sampling technique used in this study was random sampling and found 107 respondents. The analysis technique used in this study is multiple logistic regression. The research results show a significant influence between perceived susceptibility, perceived severity, perceived benefits, perceived barriers, and perceived self-efficacy with compliance. But there is no influence between cues to action on compliance. Variables included in the modeling and proven to influence pregnant women’s adherence to the COVID-19 protocol include perceived severity, perceived benefits, perceived barriers, and perceived self-efficacy, with perceived severity being the most dominant variable. So it is hoped that policy maker will consider more of perceived severity, benefits, barriers, and self-efficacy.